Exploring bikeability in a metropolitan setting: stimulating and hindering factors in commuting route environments - Wahlgren Lina; Schantz Peter (BMC, 2012)
Abstract Background Route environments may influence people's active commuting positively and thereby contribute to public health. Assessments of route environments are, however, needed in order to better understand the possible relationship between active commuting and the route environment. The aim of this study was, therefore, to assess the potential associations between perceptions of whether the route environment on the whole hinders or stimulates bicycle commuting and perceptions of environmental factors. Methods The Active Commuting Route Environment Scale (ACRES) was used for the assessment of bicycle commuters' perceptions of their route environments in the inner urban parts of Greater Stockholm, Sweden. Bicycle commuters (n = 827) were recruited by advertisements in newspapers. Simultaneous multiple regression analyses were used to assess the relation between predictor variables (such as levels of exhaust fumes, noise, traffic speed, traffic congestion and greenery) and the outcome variable (hindering - stimulating route environments). Two models were run, (Model 1) without and (Model 2) with the item traffic: unsafe or safe included as a predictor. Results Overall, about 40% of the variance of hindering - stimulating route environments was explained by the environmental predictors in our models (Model 1, R2 = 0.415, and Model 2, R 2= 0.435). The regression equation for Model 1 was: y = 8.53 + 0.33 ugly or beautiful + 0.14 greenery + (-0.14) course of the route + (-0.13) exhaust fumes + (-0.09) congestion: all types of vehicles (p ≤ 0.019). The regression equation for Model 2 was y = 6.55 + 0.31 ugly or beautiful + 0.16 traffic: unsafe or safe + (-0.13) exhaust fumes + 0.12 greenery + (-0.12) course of the route (p ≤ 0.001). Conclusions The main results indicate that beautiful, green and safe route environments seem to be, independently of each other, stimulating factors for bicycle commuting in inner urban areas. On the other hand, exhaust fumes, traffic congestion and low 'directness' of the route seem to be hindering factors. Furthermore, the overall results illustrate the complexity of a research area at the beginning of exploration.